EXCISED EMBRYO RAMBUTAN (Nephelium lappaceum L.) DAN KEPEKAANNYA TERHADAP PENGERINGAN [Desiccation Sensitivity of Rambutan (Nephelium lappaceum L.) Excised Embryo] - Usep Soetisna; Lisye Iriana Zebua (Research Center for Biology-Indonesian Institute of Sciences, 2005)
A study on desiccation sensitivity of rambutan (Nephelium lappaceum L.)excised embryo has been conducted.Excised embryos were desiccated into target moisture content of 30%, 25%, 20%, 15% and 10% respectively.Results shown that the critical level for moisture content was 20% with 60% viability and 7.431% per etmal growth rate and 929ms electric conduction Further study is needed as to investigate on how long the embryo will withstand subsequent storage treatments.